The wisdom of teams creating the high-performance organization - Katzenbach, Jon R. (New York HarperBusiness Essentials, 2003)
Motorola relied heavily on teams to surpass its competition in building the lightest, smallest, and highest-quality cell phones. At 3M, teams are critical to meeting the company's goal of producing half of each year's revenues from the previous five years' innovations. Kodak's Zebra Team proved the worth of black-and-white film manufacturing in a world where color is king.
Includes bibliographical references (p. 305-307) and index
Keywords: Teams in the workplace